Analyzing WhisperGate and BlackCat Malware: Methodology and Threat Perspective - Nicho, Mathew; Yadav, Rajesh; Singh, Digvijay (International Journal of Advanced Computer Science and Applications, 2023)
The increasing use of powerful evasive ransomware malware in cyber warfare and targeted attacks is a persistent and growing challenge for nations, corporations, and small and medium-sized enterprises. This threat is evidenced by the emergence of the WhisperGate malware in cyber warfare, which targets organizations in Ukraine to render targeted devices inoperable, and the BlackCat malware, which targets large organizations by encrypting files. This paper outlines a practical approach to malware analysis using WhisperGate and BlackCat malware as samples. It subjects them to heuristic-based analysis techniques, including a combination of static, dynamic, hybrid, and memory analysis. Specifically, 12 tools and techniques were selected and deployed to reveal the malware’s innovative stealth and evasion capabilities. This methodology shows what techniques can be applied to analyze critical malware and differentiate samples that are variations of known threats. The paper presents currently available tools and their underlying approaches to performing automated dynamic analysis on potentially malicious software. The study thus demonstrates a practical approach to carrying out malware analysis to understand cybercriminals’ behavior, techniques, and tactics.